Quality of Plague Surveillance System in Pasuruan Regency Year 2014 Based on Surveillance Attributes - Siti Malikhatin; Lucia Yovita Hendrati (Jurnal Berkala Epidemiologi, 2017)
Plague which is the zoonosis quarantine disease remains occur in Pasuruan Regency. Plague suspect was still found until year 2013. Plague surveillance that still actively conducted in Pasuruan Regency is  probably the only one plague surveillance in Indonesia. Plague surveillance consist of human and rodent surveillance. Evaluation of surveillance system is needed to improve its quality, efficiency, and usefulness. This research aimed to assess the quality of plague surveillance system in Pasuruan Regency year 2014 based on attributes which are simplicity, flexibility, acceptability, data quality, sensitivity, predictive value positive, representativeness, timeliness, and stability. The research design was evaluation study. Subjecct was plague surveillance system in Pasuruan Regency year 2014. Data were collected by interviews, observations, and document study. The obtained data and information were compared to the guidelines and recent theories then presented in narrations, tables, and figures. The research showed that the surveillance system was simple and flexible, lack of data quality and acceptability, unmeasurable sensitivity and predictive value positive, low representativeness and timeliness, and high stability. This research concluded that quality of plague surveillance system in Pasuruan Regency based on its attributes  was not good enough. The suggestion given are conduct training, supply a sufficient budgetary fund, do monitoring and evaluation periodically, disseminate information to another program and sector, also to the community, send surveillance report by e-mail, use spreadsheet software for surveillance rodent reporting, improve the report by including information about damage serum, serum less than the total of captured rodent, and report about the missing trap.